PEMBERIAN PUPUK KOTORAN AYAM DALAM UPAYA REHABILITASI TANAH ULTISOL DESA JANJI YANG TERDEGRADASI - Walida Hilwa; Darmadi Erwin Harahap; Muhammad Zuhirsyan (Politeknik Pembangunan Pertanian Medan, 2020)
Chicken manure is an organic material that is widely used as organic fertilizer which gives effect to nutrient disparity and improves soil structure that is very lacking in organic nutrients so that the problem of soil degradation is very common lately, which ultimately affects the productivity of the land. The purpose of this study was to examine alternative land management through the provision of organic fertilizer for chicken manure in Janji Village, West Bilah District, Labuhanbatu Regency. This research conducted from November 2019 until April 2020 at the Kasa House, Faculty of Science and Technology of Labuhanbatu University. Soil samples were collected from Janji Village, West Bilah District, Labuhanbatu Regency with a height of 32 meters above sea level. The research method uses the experimental method in the Kasa House, the study uses a non factorial Complete Randomized Design with 5 treatments and 4 replications: K0 = Control (without treatment), K1 = 1.5% (18.70 tons / ha), K2 = 3, 0% (27.40 tons / ha), K3 = 4.5% (46.10 tons / ha), K4 = 6.0% (60.80 tons / ha). Self-dose based on the amount of organic matter contained in the soil as much as 3%. Results of the research The provision of organic matter compost of chicken manure as much as 46.10 tons/ha to 60.80 tons/ha significantly improved soil chemical properties (soil pH, C-organic, N-total, C / N, P-available, CEC) at ultisol soil in Janji Village, West Bilah District.